SAT0559 High Expression of Cyclooxygenase-2, Prostaglandin E2 and Prostaglandin E2 Receptor Ep4 in Zygapophyseal Joints of Patients with Ankylosing Spondylitis. (10th June 2014) - Bleil, J.; Appel, H.; Maier, R.; Sieper, J.; Syrbe, U.
Abstract : Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are the first-line treatment for patients with ankylosing spondylitis (AS). They are effective in reducing signs and symptoms, and increasing evidence suggests that their sustained use may also retard radiographic progression [1, 2]. The equal efficacy of cyclooxygenase (COX)-2 selective inhibitors in AS suggests that COX-2-dependent PGE2 synthesis is involved in the pathogenesis of AS. Objectives: We studied here the expression of COX-2 and PGE2 and of the PGE2 receptors EP2 and EP4 in zygapophyseal joints of AS patients. Methods: COX-2, PGE2, EP2 and EP4 were determined by immunohistochemistry in zygapophyseal joints from 19 AS, 11 osteoarthritis patients (OA) and 12 autopsy controls (CO). COX-2 +, PGE+, EP+ and EP+ cells were detected at four different sites: within hyaline cartilage, subchondral bone plate, fibrous tissue and subchondral bone marrow. Results: Within the subchondral bone marrow, numbers of COX-2 + and PGE+ cells were higher in joints of AS patients compared to controls (p=0.0394, p=0.0138). The number of cells expressing EP2 and EP4 were also but non-significantly elevated in the bone marrow of AS patients (p=0.0630; p=0.0786). In contrast, we found in preliminary analysis very low expression of COX-2 within the cartilage, the subchondral bone and the subchondral fibrous tissue. Within the subchondral bone plate, numbers of PGE+ and EP+ cells were higher in AS (and OA) patients compared to controls (p<0.05 for all), while no significant differences were seen within the cartilage comparing AS patients and controls. Comparably very high numbers of PGE+ and EP+ cells were detected within the fibrous tissue of AS and OA patients (p=0.1902, p=0.3726). Conclusions: According to these data, COX-2 dependent PGE2 synthesis is primarily seen in the subchondral bone marrow and elevated in AS patients, and might be the target site for drugs inhibiting COX-2. References: Poddubnyy D, Rudwaleit M, Haibel H, Listing J, Marker-Hermann E, Zeidler H, et al. Effect of non-steroidal anti-inflammatory drugs on radiographic spinal progression in patients with axial spondyloarthritis: results from the German Spondyloarthritis Inception Cohort. Annals of the rheumatic diseases. 2012 Oct; 71(10):1616-1622. Wanders A, Heijde D, Landewe R, Behier JM, Calin A, Olivieri I, et al. Nonsteroidal antiinflammatory drugs reduce radiographic progression in patients with ankylosing spondylitis: a randomized clinical trial. Arthritis and rheumatism. 2005 Jun; 52(6):1756-1765. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3576